Experimental Study on the Shear Performance of Steel-Truss-Reinforced Concrete Beam-Column Joints - Dafu Cao; Jiaqi Liu; Wenjie Ge; Rui Qian (Advances in Civil Engineering)
In order to study the influence of the axial compression ratio and steel ratio on the shear-carrying capacity of steel-truss-reinforced beam-column joints, five shear failure interior joint specimens were designed. The effect of different coaxial pressure ratios (0.1, 0.2, and 0.3) and steel contents on the strain, ultimate bearing capacity, seismic performance, and failure pattern of cross-inclined ventral and chord bars in the joint core area was investigated. The experimental results show that the load-displacement hysteretic curves of all test specimens exhibit a bond-slip phenomenon. With the increase of the axial compression ratio, the ultimate bearing capacity of the joint core increases by 3.4% and 5.9%, respectively. While the ductility decreases by 10.3% and 13.1%, and the energy consumption capacity decreases by 3.2% and 5.8%, respectively. The shear capacity and ductility of the member with cross diagonal ventral steel angle in the joint core are increased by 12.9% and 13.4%, respectively. The shear capacity and ductility of the joint can be significantly improved by increasing the amount of steel in the core area. The expression of shear capacity suitable for this type of joint is obtained by fitting analysis, which can be used as a reference for engineering design.